Homologous recombination following transformation in Neurospora crassa wild type and mutagen sensitive strains - Alice L. Schroeder; Martin L. Pall; James Lotzgesell; Jacie Siino (Fungal Genetics Reports, 1995)
In filamentous fungi transformed with linear DNA, the frequency of gene replacement varies from a few percent in Neurospora crassa, where it depends on the extent of homology between the transforming DNA and the gene to be replaced, (Asch and Kinsey 1990 Mol. Gen. Genet. 22:37-43) to about 30% in Aspergillus (Miller et al. 1985 Mol. Cell Biol. 5:17-14). Yet, in the yeast, Saccharomyces cerevisiae, homologous gene replacement is the rule and ectopic integration of transforming DNA is extremely rare (Fincham 1989 Microbiol. Rev. 53:148-170). This variation could be the result of the action of one or a few genetic pathways and thus, be affected by single mutations. Mutants with altered ability to integrate transforming DNA may be sensitive to ionizing radiation, since double strand break repair is necessary for both recombination and survival after ionizing radiation damage. Therefore, we looked among the radiation-sensitive mutants, uvs-2,3,6, mus-9,11, and mei-2,3, for changes in the ability to integrate transforming DNA either ectopically or by homologous recombination. All mutant strains were extensively backcrossed to wild type strains of 74-OR23-1A background and the 74-OR23-1A strain served as a control.